Proteomic-based profiling of the leaf extracts of Ficus deltoidea / Amy Tan Bee Bee - Tan, Amy Bee Bee (2014)
Ficus deltoidea is one of the well-known herbs in Malay traditional medicine. This plant is commonly known as Mas Cotek in Malaysia. According to traditional medicinal practitioners, the decoction of the plant is able to prevent and cure various ailments. Recent pharmacological studies suggested that the aqueous extract contains pharmacologically active constituents that support the traditional use of this plant. The aim of this study is to investigate and compare the protein present in F. deltoidea var. angustifolia (SL), F. deltoidea var. trengganuensis (ML) and F. deltoidea var. kunstleri (BL) leaves aqueous extract using proteomic techniques. In sample preparation, protein precipitation is a crucial step in removing interfering compound that may affect the proteomic analysis and also to concentrate the proteins in the leaves aqueous extracts. Among the precipitation method evaluated, double precipitation method which consists of ammonium sulfate and acetone/β-mercaptoethanol precipitation was selected as the most suitable method to precipitate the protein out from the extracts as it gave higher protein purity and better band resolution on SDS-PAGE analysis. Samples obtained from this precipitation method were subjected to proteomic analysis and revealed a total of 45, 24 and 9 protein spots on the proteome of SL, ML and BL respectively. All of them are lower than 78 kDa. Proteins below 6 kDa were underrepresented on 2-D proteome profile due to the limitation of 2-D gel electrophoresis, but were revealed on SDS-PAGE proteome profile. SL proteome contains of a group of characteristic proteins in the range of 6 – 26 kDa that are not present in ML and BL proteome, whereas ML and BL have similar proteome. SELDI-TOF profiling also showed similarity in ML and BL spectrum profile with 4 signal peaks detected, while there are only 3 signal peaks obtained in SL SELDI-TOF profile. The missing signal peak at m/z 3825 had differentiated SL from ML and BL. Besides that, decoction of Ficus leaves also contains some glycoproteins which lead to the smearing background.